Discovery of substituted (4-phenyl-1H-imidazol-2-yl)methanamine as potent somatostatin receptor 3 agonists. Issue 17 (1st September 2015) - Lai, Zhong; He, Shuwen; Sherer, Edward C.; Wu, Zhicai; Yu, Yang; Ball, Richard; Hong, Qingmei; Yang, David X.; Guo, Liangqing; Li, Derun; Tuang, Quang; Chicchi, Gary G.; et al.
Graphical abstract